PENGARUH PENGETAHUAN DAN PEMAHAMAN PAJAK, TARIF PAJAK, LINGKUNGAN WAJIB PAJAK, DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI BAGI PELAKU USAHA ONLINE - Utami, Vania (Akuntabilitas, 2023)
AbstractThis study aimed to test knowledge and understanding taxation, tax rate, taxpayer’s environment, and tax sanctions on taxpayer compliance. This study uses primary data, conducted by distributing questionnaires to online business in Wilayah Jabodetabek. The sampling used in this study is convenience sampling method. The number of online businesses in Wilayah Jabodetabek are sampled in this study are 107 online businesses. The analytical method used to test the hypothesis are multiple regression anaysis using the IBM SPSS Statistics 25 application. The result showed that knowledge and understanding taxation, tax rate, and taxpayer’s environtment has positive significant effect on taxpayer compliance and tax sanctions partially had no effect on tax compliance. Knowledge and understanding taxation, tax rate, taxpayer’s environment, and tax sanctions simultaneously had an effect on taxpayer compliance.